The Impact of Ego Depletion on Practical Skills Among University Students and Psychological Intervention Strategies (Journal of Interdisciplinary Insights, 2024)
With increasing pressures in modern society, college students face significant challenges to their self-control resources, leading to widespread ego depletion. Ego depletion refers to the consumption of psychological resources following prolonged and intense self-control tasks, which in turn affects the performance of subsequent tasks. This study aims to explore the current status of ego depletion among college students, its influencing factors, and its impact on practical skills, while evaluating effective psychological intervention strategies. Through a survey of 492 students majoring in Early Childhood Care and Education from a vocational college in Weifang City, Shandong Province, the study finds that the overall ego depletion score of college students (3.02±1.471) is at a moderately low level, with no significant impact of gender, grade, only-child status, or place of origin on ego depletion (P > 0.05). Further analysis indicates that ego depletion negatively affects students' practical skills, primarily resulting in decreased execution efficiency and unstable behavior. To address ego depletion, this paper proposes a series of psychological intervention strategies, including scientific time management, mindfulness meditation, positive emotion cultivation, regular lifestyle habits, and seeking social support. These strategies can help improve college students' self-control abilities, enhance their academic and practical performance, and promote psychological well-being.